The impact of leaders' coaching skills on employees' happiness and turnover intention - Soraia Rom\~ao; Neuza Ribeiro; Daniel Roque Gomes; Sharda Singh (Administrative Sciences, 2022)
This study seeks to provide a more comprehensive understanding of how leaders with coaching skills can affect an individual's turnover intention through the mediating role of happiness. The sample includes 271 individuals from diverse organizations. Based on a survey, employees assessed their leaders' coaching skills and reported their own happiness and turnover intention. The findings demonstrate that leaders' coaching skills have a negative impact on employees' turnover intention and a positive impact on their happiness, with the latter mediating the relationship between the first two variables. Organizations should note that a leader's coaching skills are useful not only for the employee's happiness, but also for avoiding turnover intention; therefore, organizations should encourage leaders to integrate more coaching skills into their leadership styles. The identification of an employee's happiness as a mediator of the relationship between a leader's coaching skills and employees' turnover intention is an original contribution, thereby extending previous research over these topics.
Keywords: 350; happiness; leaders' coaching skills; turnover intention